The undoing - Laurenston, Shelly (Laurenston, Shelly. Call of the Crows., 2016)
A risk worth taking. No one would ever accuse Jace Berisha of having an easy life considering her husband...you know...killed her. But that was then! Now she fights for mighty Viking gods with the spectacular and vicious Crows. But things are turning very bad, very quickly because a vengeful, ancient goddess has come into the world with just one thing on her mind--ending it. And the only way they can hope to stop her is if the Crows join forces with their one-time enemies, the Protectors. A Viking Clan created to do nothing but kill every Crow they see. Thankfully, Protector Ski Eriksen is a peace loving kind of guy. Because the woman he is desperately trying to get close to is the beautiful and not-very-chatty Jace. Battling Nordic clans? Unkillable goddesses? Jace's mean-spirited dog? None of these things would ever get in the way of a true Viking!